Avaliação de cardiotoxicidade subclínica tardia em pacientes com diagnóstico prévio de linfoma não Hodgkin tratados com antraciclinas - Fusco, Daniéliso Renato [UNESP] (2015)
Background: late cardiotoxicity in non-Hodgkin lymphoma survivors (NHL) treated with anthracycline is manifested by heart failure (HF), defined by reduced left ventricular ejection fraction (LVEF). These patients may show signs suggestive of late cardiotoxicity, although not express clinic HF or reduced LVEF. The study of the cardiovascular function through the use of more sensitive diagnostic methods for the early detection of myocardial dysfunction may contribute to the prevention and treatment of cardiotoxicity. Objectives: to evaluate late subclinical cardiotoxicity signals in patients previously diagnosed with NHL treated with anthracycline through clinical and laboratory examination with cardiac biomarkers, two-dimensional transthoracic speckle tracking echocardiography, carotid ultrasound and treadmill test; to relate the derived myocardial function indexes of speckle tracking echocardiography with exercise capacity estimated by treadmill test. Methodology: non-randomized controlled trial, 1: 2, which included NHL survivors treated with anthracycline for more than one year, no previous diagnosis of HF (anthracycline group) and healthy subjects (control group), matched for sex and age. For all study participants were evaluated: clinical signs and symptoms of HF, risk factors and cardiovascular risk score, use of medications, blood biochemical tests, test with treadmill, carotid ultrasound to obtain intima-media thickness of the common carotid and transthoracic echocardiography with traditional measures including LVEF using the Simpson method, and the determination of two-dimensional global longitudinal strain (GLS) by speckle tracking. Results: the anthracycline group consisted of 28 subjects with a mean age of 52 (44; 65) years, 64% male, with a cumulative total dose of 386 (200; 400) mg/m2 of doxorubicin, and 63 subjects in the control group. The groups did not differ with respect to clinical examination, risk factors, ...